A Scoping Review of The Percutaneous Coronary Intervention: Practice Transformation for the Operational Access - Sazzad, Faizus; Rahman, Arifur (University Heart Journal, 2022)
Background: The transfemoral approach is the commonest and most widely practiced access for Percutaneous coronary intervention (PCI). However, the less invasive operational access for PCI is growing substantially and gaining popularity over the conventional practice. Although, there is little known about the true benefits regarding access for the PCI in adult Bangladeshi patients requiring coronary revascularization. This systematic review was aimed to compile literature evidence for the alternative PCI access when compared with standard transfemoral practice in our country. Method: A scoping review according to the Preferred Reporting Items for Systematic Reviews and Metaanalyses (PRISMA) guidelines was conducted. As there is a scarcity of published literature comparing transfemoral vs alternative PCI routes, this scoping review was not aimed to produce a critical appraisal rather an overview and map of synthesized evidence based on the available literature. Results: 498 articles were accessed from PubMed, BanglaJOL, and Web of Science databases. A total of seven articles were included for final analysis, comprising 1212 patients undergoing PCI at the different tertiary hospitals across the country. Among the included patients 834 PCI were performed via transfemoral access, 330 via transradial access, and 48 procedures were done via transulnar access. Conclusion: Alternative access for PCI is gaining popularity in adult Bangladeshi patients requiring coronary revascularization. It’s a rational approach for the selective population in coronary revascularization strategy. University Heart Journal 2022; 18(2): 106-117